The Use of OCW and WIKIS as Collaborative Tools for Specialized Translation - Montalbán Martínez, Nicolás (CIC. Cuadernos de Información y Comunicación, 2019)
The aim of this work is to analyse the results of the OCW project entitled Elaboración y Traducción de Textos Científicos en Geografía, given in the call R-700/2017 school year 2017/2018 by the University of Murcia. In mentioned project students are expected to acquire the subject competences working in collaborative translation assignments, encouraging participation among students. Topics are related to their professional interests and are related to other subjects, giving rise to an interdisciplinary approach and using a constructivist approach by using scaffolds and flipped classroom techniques. Contents have been uploaded to a collaborative wiki, being the professor a facilitator of the whole process. Although the impact was initially observed in the above subject, it was transferred to other subjects. It is important to stress the innovative aspect of the project which is focusing in specialized translation rather than in morphosintax and lexis.